Effect of urinary kidney injury molecule-1 levels on short-term prognosis of chronic heart failure - Geng, Like; Dang, Qun; Lv, Guo; Wang, Luzhao; He, Sanjun (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the influential elements of urinary kidney injury molecule-1 levels in chronic heart failure, and to judge its ability to predict 90-day rehospitalisation. Method: The cross-sectional case-control study was conducted from November 2020 to April 2021, at Hanzhong Central Hospital, China, and comprised adult patients having chronic heart failure with normal renal function in group A and healthy subjects in control group B. Patients in group A received anti-heart failure therapy for 1 week in hospital and were followed up for 90 days after discharge. Blood pressure (BP), kidney injury molecule-1, creatinine and serum pro-B-type natriuretic peptide levels were evaluated at baseline and 1 week after treatment in group A, while the samples were collected only at baseline in the control group B. Data was analysed using SPSS 22. Results: Of the 102 subjects, 68(66.6percent) were in group A; 44(64.7percent) males and 24(35.3percent) females with mean age 62.38±9.51 years. The remaining 34(33.3percent) subjects were in group B; 21(61.7percent) males and 13(38.2percent) females with mean age vs. 58.82±8.11 years. The urinary kidney injury molecule-1 level in group A was essentially on the increase compared to group B (p 0.05). After 1 week of treatment, the kidney injury molecule-1 level decreased compared to the baseline value in group A (p 0.05). Diastolic blood pressure and pro-B-type natriuretic peptide were the determinants of urinary kidney injury molecule-1 level, and urinary kidney injury molecule-1 level before discharge was significantly associated with rehospitalisation within 90 days (p 0.05). Conclusion: Urinary kidney injury molecule-1 level before discharge was a significant predictor of rehospitalisation within 90 days, and diastolic blood pressure and pro-B-type natriuretic peptide levels were the influencing factors of urinary kidney injury molecule-1. Also, urinary kidney injury molecule-1 levels were significantly raised in chronic heart failure. Key Words: Chronic heart failure, KIM-1, Rehospitalisation.